PERBANDINGAN DOUBLE MOVING AVERAGE DENGAN DOUBLE EXPONENTIAL SMOOTHING PADA PERAMALAN BAHAN MEDIS HABIS PAKAI - Hommy Dorthy Ellyany Sinaga; Novica Irawati (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2018)
Medical disposable is one of important support tools in medical operational and must not be out of stock in order to deliver excellent service in hospital. The pharmacy department has to forecast the demand to supply information for decision making in budgeting. In this paper, is comparing double moving average and double exponential smoothing method for 3 ml spuit for time series 01 January to 30 June 2017. The accuracy of forecasting is the most important and it can be measure with MAPE (Mean Absolute Percentage Error) and RMSE (Root Mean Square Value). The smallest value of MAPE and RMSE is having the high accuracy of forecasting. The double moving average method has the smallest MAPE = 0.353 and RMSE = 95.8 compare to Exponential Smoothingand be the best option to use as method to forecast the medical disposable supply demand.